An Integrated Learning Process Model for Enhancing Innovation Creative Systematic Thinking and Humanized Health Care of Lecturers and Support Personnel at Sirindhorn College of Public Health, Ubon Ratchathani Province - Sontichai, Aunnop; Boonsu, Thanomsak; Thanee, Nithit; Kramutkant, Rungaroon; Khumkaew, Jinda; Wongyai, Sirisuda (Journal of Research and Curriculum Development, 2023)
This participation action research aims to develop an integrated learning process model for enhancing creative and systematic innovative thinking and the humanized care of instructors and support personnel at Sirindhorn College of Public Health in Ubon Ratchathani province by using a learning process based on research articles, After Action Review (AAR), and reflection on creative ideas using the three-basket technique as the method. The sample in this study was 640. A questionnaire was the tool used in this study and verified with a content validity from three reviewers as >0.5. The reliability of the questionnaires was calculated as a Cronbach’s alpha coefficient as 0.79. The findings indicated that the results of model development were composed of the following: (1) the principles of the model; (2) the objectives of model; (3) the procedure of model, which consisted of five steps, as follows: (A) learning to enhance a growth mindset; (B) passion for the development of creative innovation; (C) innovation development based on research studies; (D) reflections and lesson learned, and (E) knowledge management for creating innovation; (4) model evaluation; and (5) supporting factors. The results of the efficacy evaluation on the creative model for producing innovations from lecturers and support staff were at a high level overall (M = 4.49, S.D. =0.44) while humanized health care average as a whole at highest level (M = 4.51, S.D. =0.54). Qualitative data were analyzed using three-baskets technique was presented so that the model helped lecturers and support personnel practice more listening without any judgment. The rules of conversation were that “someone speaks, everyone should listen to the speakers deeply. If the listeners would like to be a speaker, he/she should wait times without any interrupts, and could reflect his/her ideas in a polite way with their honest. This method would help lecturers and support staff develop positive thinking in terms of enhancing student competency and becoming perfect humans, as well as supporting the identity of service-mindedness with humanized care.